A new method for amino acid geochronology of the shell of the bivalve mollusc Arctica islandica - M. L. G. Conti; P. G. Butler; D. J. Reynolds; T. Trofimova; J. D. Scourse; K. E. H. Penkman (Geochronology, 2024)
The bivalve mollusc Arctica islandica can live for hundreds of years, and its shell has provided a valuable resource for sclerochronological studies and geochemical analyses for understanding palaeoenvironmental change. Shell specimens recovered from the seabed need to be dated in order to aid sample selection, but existing methods using radiocarbon dating or cross-dating are both costly and time-consuming. We have investigated amino acid geochronology (AAG) as a potential alternative means of providing a less costly and more efficient range-finding method. In order to do this, we have investigated the complex microstructure of the shells, as this may influence the application of AAG. Each of the three microstructural layers of A. islandica have been isolated and their protein degradation examined (amino acid concentration, composition, racemization, and peptide bond hydrolysis). The intra-crystalline protein fraction was successfully extracted following oxidation treatment for 48 h, and high-temperature experiments at 140 °C established coherent breakdown patterns in all three layers, but the inner portion of the outer shell layer (iOSL) was the most appropriate component due to practicalities. Sampling of the iOSL layer in Holocene shells from early and late ontogeny (over 100–400 years) showed that the resolution of AAG is too low in A. islandica for within-shell age resolution. However, analysis of 52 subfossil samples confirmed that this approach could be used to establish a relative geochronology for this biomineral throughout the whole of the Quaternary. In the late Holocene the temporal resolution is ∼1500–2000 years. Relative dating of 160 dredged shells of unknown age was narrowed down using AAG as a range finder, showing that a collection of shells from Iceland and the North Sea covered the middle Holocene, late Holocene, later and post-medieval (1171–1713 CE), and modern day. This study confirms the value of A. islandica as a reliable material for range finding and for dating Quaternary deposits.